The Arve Valley and Environmental Health: From Therapeutic Imagination to Eco-anxiety - Alexandre Savioz (Revue de Géographie Alpine)
This article contrasts two periods of time in the Arve Valley, during which particular attention was paid to the links between human health and the environment, but with diametrically opposed perceptions. Historically, the Plateau d'Assy in the Arve Valley was a major healthcare destination, particularly specializing in the treatment of tuberculosis between the 1920s and 1970s. From the 19th century onwards, a collective imagination emerged around the myth of clean air of the mountains. Alpine regions broadly benefited from being considered particularly sanitary, and this was the engine of local tourism until the 1970s. Though the therapeutic characteristics of the mountains still exist today, scientific analyses carried out from the 1990s have underlined the great vulnerability of the Alpine valleys to atmospheric pollution. This is the case of the Arve Valley which, over the past two decades, has become infamous in the media for its poor air quality. Now understood to be a significant public health issue, air pollution in this region has become a major source of fear and anxiety for part of the local population. Though this contrasts sharply with past therapeutic representations of the mountains as mentioned above, current fears around air quality in the Arve Valley find themselves echoed in broader societal debates around environmental health and eco-anxiety.